Non-perturbative orientifold transitions at the conifold - Hori, Kentaro; Walcher, Johannes (Arxiv, 2005)
After orientifold projection, the conifold singularity in hypermultiplet moduli space of Calabi-Yau compactifications cannot be avoided by geometric deformations. We study the non-perturbative fate of this singularity in a local model involving O6-planes and D6-branes wrapping the deformed conifold in Type IIA string theory. We classify possible A-type orientifolds of the deformed conifold and find that they cannot all be continued to the small resolution. When passing through the singularity on the deformed side, the O-plane charge generally jumps by the class of the vanishing cycle. To decide which classical configurations are dynamically connected, we construct the quantum moduli space by lifting the orientifold to M-theory as well as by looking at the superpotential. We find a rich pattern of smooth and phase transitions depending on the total sixbrane charge. Non-BPS states from branes wrapped on non-supersymmetric bolts are responsible for a phase transition. We also clarify the nature of a Z_2 valued D0-brane charge in the 6-brane background. Along the way, we obtain a new metric of G_2 holonomy corresponding to an O6-plane on the three sphere of the deformed conifold.